2018
DOI: 10.33490/jkm.v4i2.79
|View full text |Cite
|
Sign up to set email alerts
|

Studi Literatur: Akupresur Titik P6 dalam Mencegah dan Mengurangi Mual dan Muntah Postoperasi

Abstract: Postoperative nausea and vomiting are defined as nausea and  vomiting occurring within 24 hours after surgery and is one of the complications of general anesthesia and neuroaxial anesthesia.This is still a major concern concern in patients undergoing surgery because it increases morbidity due to dehydration, electrolyte disturbance, aspiration, wound pain, pneumothorax, subcutaneous emphysema, esophageal rupture, which is resulting in delayed recovery, increased cost, and patient dissatisfaction. Although naus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…These limitations are related to the availability of human resources in the field and local government participation in the Bribin watershed's management plans [60]. A study conducted by Harmiati, et al [61] has concluded that some district governments failure to realize the institutions aspect in IWM is caused by the absence of a legal rule, lack of coordination, low participation, a top-down approach, and a lack of transparency in watershed management. Conflicts of interest between central and local governments and/or between local governments have exacerbated the situation upstream.…”
Section: Institutionmentioning
confidence: 99%
“…These limitations are related to the availability of human resources in the field and local government participation in the Bribin watershed's management plans [60]. A study conducted by Harmiati, et al [61] has concluded that some district governments failure to realize the institutions aspect in IWM is caused by the absence of a legal rule, lack of coordination, low participation, a top-down approach, and a lack of transparency in watershed management. Conflicts of interest between central and local governments and/or between local governments have exacerbated the situation upstream.…”
Section: Institutionmentioning
confidence: 99%